PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN SISTEM REM SISWA KELAS XI TEKNIK KENDARAAN RINGAN SMK PIRI SLEMAN TAHUN AJARAN 2014/2015 - Yudhia Putra Wardana; Subagyo Subagyo (Jurnal Taman Vokasi, 2016)
Application Demonstration Method To Increase Activity And Result Of Study Subject Brake System Class XI Technical Light VehicleÂ  Student Of SMK PIRI Sleman School year 2014/2015. Thesis Education Course Mechanical Engineering Faculty of Teacher Training and Education Sciences Sarjanawiyata Tamansiswa University Yogyakarta in 2015.The purpose of this research to increase student activity and results of study subjects brake system class XI student of SMK TKR PIRI Sleman in the academic year 2014/2015 using the demonstration method.This research is a classroom action research, The object of this research is 26 student a class XIÂ  TKR A. In the process of learning to apply the method demonstration. This classroom action research 4 steps being taken including planning, implementation, observation and reflection. Systematic implementation of this study apply 3 cycles, the data collection methods used by the focus that tests and observation. The data analysis technique is qualitative descriptive dilakuakan that consists of data collection, data reduction and conclusion.This class research results show that in these subjects the brake system can enhance the activity of students and student learning outcomes than the average percentage of the three aspects of the observations of each cycle is 34.8% on a pre cycles, 53.8% in the first cycle, 76,92% in cycle II, and 84.61% in the third cycle. Improving student learning outcomes in subjects with the application of the brake system that is based on the method of demonstration class average an increase of 64.23 at pratindakan / prasiklus, 69.61 in the first cycle, the second cycle 76.92, and 79.03 in the third cycle. Based KKM students who completed the pre-action / pre-cycle as much as 9 students, students who completed the first cycle as many as 14 students, students who completed the second cycle as many as 19 students, and students who completed the third cycle as many as 22 students. Application of the method of demonstration is very influential in improving student learning activities in the learning process to understand the brake system. It is characterized by the passage of the activities of students as well as the rising value of the tests performed. Application of the method demonstration on subjects understand the brake system can enhance the activity of students and student learning result.